Sistem Informasi Pengarsipan Surat Masuk dan Surat Keluar Pada Badan Pengelolaan Keuangan dan Aset Daerah - Fitri Annisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
A letter is a means of communication to convey written information by one party to another and also functions as a reminder. Seeing the importance of a letter to be managed properly, the presentation of the latest information regarding management is very important because it plays a major role in supporting the implementation of activities and other functions. Management of letter data in a company that is relatively large is certainly a problem, if the management of letters still uses manual methods. For this reason, it is necessary to think about developing an effective system that is considered capable of helping in handling the process of administering letter data which includes storage, changes and accuracy and speed in its presentation. Here the author focuses on designing an information system for incoming and outgoing letters at the Financial Management and Regional Asset Agency of North Sumatra Province using the Visual Studio 2008 Program. The use of this system is to make it easier for employees when creating incoming and outgoing letter report data